Implementasi Perjanjian Kerja Sama antara Badan Narkotika Nasional Provinsi Sumatera Barat dan Kepolisian Daerah Sumatera Barat dalam Program P4GN di Provinsi Sumatera Barat - Shafira Apriananda; Hasbullah Malau (YASIN, 2026)
Narcotics abuse and illicit trafficking constitute public issues that require interagency coordination, particularly between BNNP and Polda. Although coordination in the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN) Program has been widely discussed, studies on the implementation of cooperation agreements between BNNP and Polda in regional contexts remain limited. This study aims to analyze the implementation of Cooperation Agreement Number PKS/03/Ka/X/HK.00/2020/BNNP between BNNP West Sumatra and Polda West Sumatra in the P4GN Program. This study used a descriptive qualitative approach involving 14 informants selected using purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that the implementation of the cooperation agreement had not run optimally. The six scopes of cooperation, namely data exchange, prevention, law enforcement, police medical services, human resource capacity building, and personnel assistance, had not been fully implemented formally. Cooperation took place more informally, situationally, and based on personal relationships. These findings confirm that revitalization of the cooperation agreement is needed through the formulation of joint technical SOPs, regular coordination forums, a documented data exchange system, cross-institutional training, and continuous monitoring and evaluation to strengthen the effectiveness of P4GN Program implementation in the regions.